Paediatric out-of-hospital clinical deterioration: a mixed-methods scoping review protocol - Tim Coats; Damian Roland; Sara Alsuwais; Gregory Adam Whitley; Alanowd Alghaith (BMJ Publishing Group, 2024)
Introduction In pre-hospital settings, identifying a deteriorating child can be challenging, especially considering that the proportion of paediatric patients with acute illnesses is lower compared with adults. This challenge is exacerbated in pre-hospital settings, where information might be scarce. Physiological alterations indicating changes in a patient's condition can be detected hours preceding a cardiac arrest. Therefore, maintaining continuous monitoring of the patient's clinical condition is crucial to detecting any physiological changes promptly, facilitating early identification of critical illness. This scoping review aims to assess the extent, range and nature of published research related to recognising paediatric out-of-hospital clinical deterioration by pre-hospital staff.Methods and analysis This scoping review is registered with the Open Science Framework. The review will follow the Joanna Briggs Institute's (JBI) methodology for scoping reviews. A systematic search of relevant databases (MEDLINE, EMBASE, Web of Science, CINAHL and Scopus) will be conducted. In this scoping review, all types of study designs including quantitative and qualitative studies will be considered. The inclusion is limited to English-language studies published between January 1990 and March 2024. Two independent reviewers (AG and SS) will conduct a thorough screening of titles and abstracts against the pre-defined inclusion criteria for the review. For the selected citations, the full texts will undergo detailed assessment by the two reviewers, ensuring alignment with the inclusion criteria. A quality assessment of the included studies will be done using the Mixed Methods Appraisal Tool. The findings will be presented using diagrams or tables, supplemented by narrative summaries following the JBI guidelines.Ethics and dissemination Ethical approval is not required. The findings will be disseminated through publication in a peer-reviewed journal and presentation at conferences and/or seminars.